Phytochemical Composition and Antioxidant Activity of Maerua angolensis used for Cancer Treatment in Funakaye Local Government, Gombe State, Nigeria - I. I., Hamma; U. M., Jajere; A.M., Gimba (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Maerua angolensis leaves and stembark have been used traditionally for the treatment of various diseases including cancer. Despite its widespread use and numerous reported beneficial uses, there is a few research on its antioxidant potential. The present study was therefore conducted to evaluate the qualitative and quantitative phytochemical constituents and antioxidant activity of the methanol leaves and stembark extracts. Phytochemical screening was carried out using standard methods and procedures as described by Evans for the identification of phytochemicals. The antioxidant properties of methanol extracts were investigated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity and ferric reducing antioxidant power (FRAP). The phytochemical screening of M. angolensis leaves revealed the high concentration of steroids, saponins, coumarin, terpenoid, phenols, flavonoids, cardiac glycosides, tannins and appreciable amount of alkaloids while steroids, terpenoid, phenols, cardiac glycosides and tannins were found at high concentration with appreciable amount of saponins and alkaloids in the stem bark but coumarin and flavonoid were not detected. The activity of the extract against the free radicals was concentration dependent. The result revealed a linear correlation between the extract and its polyphenolic contents.The reducing ability of the extract also occurred in a dose dependent manner. The study provides evidence that the leaves and stembark of M. angolensis contain essential constituents which may serve as natural antioxidants. Therefore, it could be concluded that the plant contains phytochemicals needed in the treatment and management of various diseases.